Media Flashcard Dalam Pengajaran Kosakata Bahasa Inggris - Ayu Melati Ningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This community service aims to help certain communities in several activities. One of the services is carried out at TK Kemala Bhayangkari 03 Medan. This community service is Flash card Media in Teaching English vocabulary. Given the important role of vocabulary in language, learning vocabulary is a very important concern in learning English. For kindergarten students learning vocabulary in English is not an easy thing to get new vocabulary that is incorporated into teachers who have difficulty in learning vocabulary.The community service team is interested in holding this service by trying to use flashcard media in learning English with the hope that the students of TK Kemala Bhayangkari 03 Medan can add new vocabulary in English through flashcard media.